2015
DOI: 10.1007/s00428-015-1724-9
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical clustering identifies a subgroup of colonic adenocarcinomas expressing crypt-like differentiation markers, associated with MSS status and better prognosis

Abstract: The aim of this study was to identify in the group of colonic adenocarcinomas, not otherwise specified (NOS), subgroups of oncogenetic and prognostic significance based on the expression of immunohistochemical markers of epithelial cell differentiation of the gastrointestinal tract. Hierarchical clustering analysis of 122 adenocarcinomas (NOS) identified four clusters based on how closely their profile of immunohistochemical expression of differentiation markers was related: (i) a major cluster of 83 adenocarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 33 publications
0
12
1
1
Order By: Relevance
“…Our analysis of the prognostic role of CK7 was performed retrospectively and without knowledge of BRAF status. Droy-Dupré et al clustered 122 CRCs describing CK20 + CK7-CDX2 + MMR + so called "crypt-like carcinoma" and minor MUC5AC + CK7+/-subtype with foveolar gastric phenotype; the latter cluster of CRCs displayed worse prognosis [20]. However, this study is not directly comparable to ours because of different way of cohort grouping based on different examined markers.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Our analysis of the prognostic role of CK7 was performed retrospectively and without knowledge of BRAF status. Droy-Dupré et al clustered 122 CRCs describing CK20 + CK7-CDX2 + MMR + so called "crypt-like carcinoma" and minor MUC5AC + CK7+/-subtype with foveolar gastric phenotype; the latter cluster of CRCs displayed worse prognosis [20]. However, this study is not directly comparable to ours because of different way of cohort grouping based on different examined markers.…”
Section: Discussioncontrasting
confidence: 60%
“…It is taken as a good distinguishing marker for primary lung cancer and CRC metastatic spread to the lungs, but not all CRCs lack CK7 expression. Various studies have shown that the rate of CK7-positivity can vary from 0 to 22% [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…It has been applied to identify subgroups of cells and animals based on marker protein expression or behavioural parameters. 19, 20 Hierarchical clustering analysis was carried out with SPSS (SPSS version 21, IBM SPSS, Chicago, IL, USA) to separate vehicle- or paroxetine-treated mice into subgroups. Based on FST immobility time, three subgroups that include long-time floating, intermediate-time floating and short-time floating groups were stratified for each treatment condition (vehicle or paroxetine).…”
Section: Methodsmentioning
confidence: 99%
“…HCA is a method to build and split different cluster hierarchies. It has been applied to identify sub-groups of cells and animals based on marker protein expression or behavioral parameters 40 41 . HCA was carried out with SPSS (SPSS version 21, IBM SPSS Inc., Chicago, IL, USA) to separate paroxetine-treated sub-groups of mice based on FST floating time.…”
Section: Methodsmentioning
confidence: 99%